1997
DOI: 10.1136/gut.40.6.767
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical coding in the small intestine of patients with Crohn's disease.

Abstract: Background-There have been conflicting results regarding the effect of Crohn's disease on the neurochemical composition of the enteric nervous system. Aims-To examine the effect of Crohn's disease on the neurochemical composition of enteric nerve fibres and celi bodies using whole mount preparations ofhuman ileum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
136
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 31 publications
10
136
2
1
Order By: Relevance
“…Percentage of VIP, PACAP and NPY-ergic neurons found in the myenteric plexus in control and pathological sections. there is an increase in the density of nerve elements containing VIP in the wall of the small and the large intestine [11,13]. On the other hand, observations related to the same disease suggest that there are no similar changes in the density of nerve elements containing VIP in the layers of the intestinal wall [29].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Percentage of VIP, PACAP and NPY-ergic neurons found in the myenteric plexus in control and pathological sections. there is an increase in the density of nerve elements containing VIP in the wall of the small and the large intestine [11,13]. On the other hand, observations related to the same disease suggest that there are no similar changes in the density of nerve elements containing VIP in the layers of the intestinal wall [29].…”
Section: Discussionmentioning
confidence: 93%
“…Investigations of the enteric nervous system in inflammatory diseases of the large intestine have shown morphological changes in this system. These changes are mostly related with increase, or decrease the number of neurons and density of nerve fibres containing neuropeptides [11][12][13][14][15][16]. As yet there is no data in the literature dealing with the problem of changes in the innervation of human organs affected by cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that all these observations are at variance with other functional and immunohistochemical studies. Indeed Tomita et al (1998) reported that the colon from patients with UC was more strongly innervated by NANC inhibitory nerves, with NO as major neurotransmitter, than was the normal colon and Belai et al (1997) observed increased VIP, NOS and PACAP immunoreactivity in the myenteric plexus and nerve ®bres of the circular muscle layer of the a icted segment of the ileum of patients with Crohn's disease. The reason for this discrepancy is unclear but it would be of interest to study the role of VIP-ergic neurotransmission in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies have added important information by showing that the content of noradrenaline and neuropeptides in nerve ®bres and neurons can also be altered in patients with in¯ammatory bowel disease (IBD) (Bjorck et al, 1989;Belai et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoreactivity for VIP decreases and substance P increases in tissues from colon of inflammatory bowel disease (IBD) patients compared to controls (Mazumdar and Das 1992;Neunlist et al 2003;Vento et al 2001). Additionally, immunoreactivity for VIP, NO synthase, and neuropeptide Y (NPY) increases in tissues from the ileum of Crohn's disease patients compared to controls (Belai et al 1997).…”
Section: Effects Of Colitis On the Ensmentioning
confidence: 99%